2015
DOI: 10.1186/s13071-015-1005-0
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural adaptations of argulid parasites (Crustacea: Branchiura) to major challenges in their life cycle

Abstract: Fish lice (Argulus spp.) are obligate ectoparasites, which contrary to most aquatic parasites, retain the ability to swim freely throughout the whole of their life. In fish farms, they can quickly increase in numbers and without effective control cause argulosis, which results in the reduced growth and survival of their fish hosts. The morphology of Argulus spp, including their sensory organs, is suitable for both parasitism and free-swimming. By spending a considerable amount of time away from their host, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Oliveira et al (2017) reported that in 13 host species of the Jari River (state of Amapá), the prevalence of parasites was 63.8%; they collected 399 parasite specimens. However, the diversity of crustacean parasites and their levels of infestation can be influenced by various factors relating to the biology of parasites and hosts, and by environmental factors, among others (CARVALHO et al, 2003;MAMANI et al, 2004;FONTANA et al, 2012;ALSARAKIBI et al, 2014;MIKHEEV et al, 2015;VASCONCELOS & TAVARES-DIAS, 2016). Fish hosts may be are used by these parasites for transportation (CARVALHO et al, 2003), which could be facilitated by migrating fish species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oliveira et al (2017) reported that in 13 host species of the Jari River (state of Amapá), the prevalence of parasites was 63.8%; they collected 399 parasite specimens. However, the diversity of crustacean parasites and their levels of infestation can be influenced by various factors relating to the biology of parasites and hosts, and by environmental factors, among others (CARVALHO et al, 2003;MAMANI et al, 2004;FONTANA et al, 2012;ALSARAKIBI et al, 2014;MIKHEEV et al, 2015;VASCONCELOS & TAVARES-DIAS, 2016). Fish hosts may be are used by these parasites for transportation (CARVALHO et al, 2003), which could be facilitated by migrating fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Fish hosts may be are used by these parasites for transportation (CARVALHO et al, 2003), which could be facilitated by migrating fish species. However, this low prevalence of parasites in the hosts of the Matapi River may be due to the influence of daily tides from the Amazon River, considering that certain crustacean parasites respond to water movement to reach their hosts (MIKHEEV et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Argulids are free swimming ectoparasites that must swim to attach to a host; therefore, a bigger fish presumably offers a larger target for attachment. Additionally, bigger fish produce larger wakes than small fish [51] that may decrease water flow around them thereby reducing the risk of the parasite being distributed downstream [52]. The water of the Pascagoula River is also very turbid and a bigger fish would also cast a larger shadow than a smaller fish that may help A. flavescens ambush it during daylight hours [53].…”
Section: Discussionmentioning
confidence: 99%
“…For much of the Fall of 2017 the Pascagoula River experienced increased flow relative to 2016, 2018, and 2019. This resulted in fewer Gulf sturgeon captured, but could have also prevented A. flavescens from finding and attaching to Gulf sturgeon since the increased flow may have dispersed the parasites downstream or made swimming more difficult [52].…”
Section: Discussionmentioning
confidence: 99%